Examining the Political Influences on School Governance in South Africa: A Case Study of the Zululand District - Nyawo, B G; Buthelezi, Alan B; Khumalo, Nontobeko Prudence; Ajani, Oluwatoyin Ayodele (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
This research examines the impact of political party affiliations and interference on school management in the Zululand District of South Africa. Using an interpretive research approach and qualitative methods, including an extensive review of existing literature and data collection through interviews, the study conducts semi-structured interviews with 21 individuals from three public primary schools. It also explores the influence of political factors on School Governing Bodies (SGBs), including their involvement in party politics and the challenges they face in enhancing their capacities. The findings confirm significant political interference in school governance, particularly in rural areas where political affiliations influence decision-making. SGBs often align themselves with political parties, leading to governance inefficiencies and conflicts among parent governors. Through the lens of participatory democratic theory, the study reveals governance capture in rural schools, with discriminatory practices and corruption arising as consequences of political intervention. The recommendations call for empowering SGBs to navigate political pressures through policy reforms, ensuring autonomy for parent governors, and reassessing the permissible extent of political influence within the governance framework. Additionally, the Department of Basic Education (DBE) is urged to address socioeconomic factors exacerbating corruption and to uphold integrity within school governance structures. By addressing the influence of politics and enhancing transparency, the DBE can cultivate a more equitable and effective educational environment for rural South African students.